SEOMAS: An Ontology-Based Multi-Agent System for Capturing Semantics of Software Project Information - Pakdeetrakulwong, Udsanee; Wongthongtham, Pornpit; Sae-Lim, S.; Naqvi, H. (2017)
© 2016 IEEE.A software development project produces a large volume of software artefacts. However, these are in syntactic form so their structures are not conducive to an understanding of the semantics, and therefore may create ambiguities (e.g. incorrect or different interpretations). This problem is particularly large in a distributed software development context where project members are geographically dispersed. Furthermore, in this type of setting, information related to the software project is scattered across various, unlinked software repositories. This results in two main challenges. First, this software project information is not readily accessible because of its dispersal. Second, there is a lack of integration among relevant software artefacts. Previous research efforts have attempted to address these issues by capturing software project information and structuring it in conceptualised form. However, most of the proposals are based on a manual or semi-automatic approach, resulting in tasks being more laborious for team members. In this paper, we propose a systematic approach to automatically capture the semantics of software project information (i.e. source code artefacts) by means of the semantic annotation process. The Software Engineering Ontology is utilised to provide domain knowledge and the multi-agent approach is applied to automate the process. Once software project information has been captured and structured according to the ontology, it is in machine understandable and processable form and can be subsequently used by software agents. They can read and process this information in order to provide active support for dispersed team members to clarify any ambiguity resulting from remote communication, to address major software development issues, and to facilitate effective and efficient coordination.